Characterization of Carbapenem-Resistant Acinetobacter baumannii Strains Isolated from Hospitalized Patients in Palestine - Regeen Handal; Lulu Qunibi; Ibrahim Sahouri; Maha Juhari; Rula Dawodi; Hiyam Marzouqa; Musa Hindiyeh (International Journal of Microbiology, 2017)
The American Centers for Disease Control and Prevention (CDC) recognizes Acinetobacter baumannii as a source of global outbreaks and epidemics especially due to its increasing resistance to commercially available antibiotics. In this study, 69 single patient multidrug resistant isolates collected from all over Palestine, except Gaza, were studied. All the isolates were resistant to all the β–lactam antibiotics including the carbapenems. Of the 69 isolates, 82.6% were positive for blaOXA-23, 14.5% were positive for blaOXA-24, and 3% were positive for blaOXA-58. None were positive for blaOXA-143 and blaOXA-235. In addition, 5.8% and 0% were positive for blaNDM and blaKPC, respectively. Of the 69 isolates, none were positive for the aminoglycoside aphA6 gene while 93% were positive for the aphA1 gene. The acetyltransferases aacC1 and aacA4 genes tested positive in 22% and 13% of the isolates, respectively. The ompA biofilm-producing virulence gene was detected in all isolates. Finally, Multilocus Sequence Typing (MLST) of 13 isolates revealed that more than one strain of A. baumannii was circulating in Palestinian hospitals as results revealed that 7 isolates were of ST208, 2 isolates ST218, 1 isolate ST231, 1 isolate ST348, and 2 new Sequence Types. The detection of these drug resistant pathogens is a reminder of the importance of active surveillance for resistant bacteria in order to prevent their spread in hospital settings.